2023
DOI: 10.1002/adfm.202212016
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid‐Deferoxamine Self‐Polymerization Coating on Ti Implant Promotes Osteointegration by Synergetic Regulation of Multi‐Pathways in ONFH Mechanism

Abstract: Osteonecrosis of the femoral head (ONFH) is a common but sophisticated multifactorial disease. In this study, the genomic characteristics of ONFH from the sequencing is first analyzed. Excepting ischemia and inflammation, some of differentially expressed genes (DEGs) are connected with autophagy. So, they are taken as the breakthrough points to design an auto polymerization coating of caffeic acid with grafting deferoxamine (DFO) and strontium on Ti substrate. In vitro cells and in vivo immunofluorescence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Previous reports indicated that DFO could potentially enhance vascularization and bone regeneration in bone fracture models. , Hypoxia-inducible factor-1 (HIF-1α) is critical for the regulation of genes involved in angiogenesis and osteogenesis. The DFO treatment could activate a range of pro-angiogenic genes critical for angiogenesis, including vascular endothelial growth factor (VEGF) .…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports indicated that DFO could potentially enhance vascularization and bone regeneration in bone fracture models. , Hypoxia-inducible factor-1 (HIF-1α) is critical for the regulation of genes involved in angiogenesis and osteogenesis. The DFO treatment could activate a range of pro-angiogenic genes critical for angiogenesis, including vascular endothelial growth factor (VEGF) .…”
Section: Resultsmentioning
confidence: 99%
“…As a vascular endothelial relaxing factor, NO serves as a regulatory signal for angiogenesis [8]. Related studies have shown that the pro-angiogenic effects of NO were mainly through promoting embryonic cells to be involved in new blood vessel formation [4].…”
Section: Combined Effects Of Cs/pda Hydrogel and Dfo On The Huvec Beh...mentioning
confidence: 99%
“…Specifically, DFO can simulate a hypoxic environment that up-regulates hypoxia-inducible factor-1α (HIF-1α) signal transduction and the expression level of its downstream angiogenic factor vascular endothelial growth factor (VEGF) [5][6][7]. Li et al [8] loaded DFO via caffeic acid on the Ti surface and demonstrated that DFO upregulated the expression of HIF-1α in MSCs and HUVECs by receptors of TGF-β and TNFR on cell membranes. However, directly loading DFO on an orthopedic Ti implant is challenging in clinical applications as a result of the short half-life of DFO and the initial burst release [9,10].…”
Section: Introductionmentioning
confidence: 99%